2020
DOI: 10.1248/bpb.b19-00694
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Properties of JTE-952, an Orally Available and Selective Colony Stimulating Factor 1 Receptor Kinase Inhibitor

Abstract: Colony stimulating factor 1 (CSF1) receptor (CSF1R) is a receptor protein-tyrosine kinase specifically expressed in monocyte-lineage cells, such as monocytes and macrophages. In this study, we characterized the pharmacological properties of an azetidine compound, JTE-952 ((2S)-3-{[2-({3-[4-(4-cyclopropylbenzyloxy)-3methoxyphenyl]azetidine-1-yl}carbonyl)pyridin-4-yl]methoxy}propane-1,2-diol), which is a novel CSF1R tyrosine kinase inhibitor. JTE-952 potently inhibited human CSF1R kinase activity, with a half ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…We then evaluated the inhibitory effect of orally administered JTE-952 on bone destruction and joint inflammation in the CIA model. JTE-952 was administered before disease onset (days [22][23][24][25][26][27][28][29][30][31][32][33][34][35] and significantly and dose-dependently suppressed the bone destruction score and TRAP-positive cell number in the knee joints at doses of ≥3 mg/kg. The disease severity after treatment with 30 mg/kg JTE-952 was almost identical to that in the normal group, in which arthritis was not induced.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We then evaluated the inhibitory effect of orally administered JTE-952 on bone destruction and joint inflammation in the CIA model. JTE-952 was administered before disease onset (days [22][23][24][25][26][27][28][29][30][31][32][33][34][35] and significantly and dose-dependently suppressed the bone destruction score and TRAP-positive cell number in the knee joints at doses of ≥3 mg/kg. The disease severity after treatment with 30 mg/kg JTE-952 was almost identical to that in the normal group, in which arthritis was not induced.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous small-molecule CSF1R inhibitors have been developed that inhibit both joint inflammation and inflammatory bone erosion in animal models of arthritis, but these are limited by poor kinase selectivity. 21) JTE-952 is a novel, orally available type II kinase inhibitor of CSF1R developed by Japan Tobacco Inc. 22) JTE-952 clearly inhibits human CSF1R kinase activity (at an IC 50 of 11.1 nmol/L) in vitro, with no obvious inhibitory activity against other kinases, except tropomyosin-related kinase A. 23) JTE-952 (≥3 mg/kg administered orally) has an anti-inflammatory effect in vivo in mice, evident as the suppression of CSF1-mediated enhancement of lipopolysaccharide (LPS)induced TNF-α production.…”
Section: Introductionmentioning
confidence: 99%
“…The potent inhibitory activity of JTE‐952 against the 50 kinases was on human KIT (36% inhibition at 1000 nM). [ 76 ]…”
Section: Therapeutic Importance Of Molecules Containing the Azetidine Heterocyclementioning
confidence: 99%
“…[18] Moreover, azetidine containing derivatives were found to have a specific inhibitor activity against colony stimulating factor 1 receptor (CSF1R) and also useful in treating various human inflammatory diseases and arthritis. [19] Molecules having substitutions at 3 rd position of azetidine are the utmost important part of various prospective therapeutic molecules. [20] Inspired by the various versatile applications of azetidine derivatives, an initiative was made in search of novel azetidine derivatives to explore more potent and less toxic anticancer medicines.…”
Section: Introductionmentioning
confidence: 99%
“…Literature survey revealed that several derivatives of azetidine have been reported to show wide range of biological activity such as antibacterial, [9] antiobesity, [10] anticancer, [11] analgesic, [12] dopamine antagonist, [13] antimalarial, [14] antischizophrenic, [15] antioxidant, [16] antidiabetic activities [17] and also useful for the treatment of central nervous system disorders [18] . Moreover, azetidine containing derivatives were found to have a specific inhibitor activity against colony stimulating factor 1 receptor (CSF1R) and also useful in treating various human inflammatory diseases and arthritis [19] . Molecules having substitutions at 3 rd position of azetidine are the utmost important part of various prospective therapeutic molecules [20] …”
Section: Introductionmentioning
confidence: 99%